Osun State Independent Shari‘Ah Panel: A Template for Alternative Dispute Resolution for Nigerian Muslims - Abdulwahab Danladi Shittu; Abdullateef Abdulazeez Aniyan (Research Synergy Foundation, 2026)
The introduction of Shariah in 1999 by Zamfara State Governor Senator Sani Yarima spurred the creation of Independent Shariah Panels in states where the full implementation of Shariah law proved challenging. These panels, operating independently of Nigeria's formal legal system, address civil disputes such as inheritance, marriage, and divorce within the Muslim community. The competence of the panel in resolving marital conflicts remains a concern. This paper focuses on the relevance and impact of the Osun State Independent Shariah Panel, which provides an alternative legal framework for the adjudication of civil cases involving Muslims in Osun State. Using descriptive and historical research methods, the paper evaluates the panel's contributions to the judicial, social, and cultural systems of society. The role of the panel in reducing communal crises and matrimonial conflicts within the community is also assessed. Additionally, the study examines the legal and social implications of the panel's operation in a secular legal environment, highlighting its relationship with the formal courts and the challenges of legitimacy and enforceability. The study finds that the panel effectively resolves disputes and has gained the trust of both Muslims and non-Muslims alike. Its contribution to promoting peace could be further strengthened if its jurisdiction were expanded to include criminal cases. Nevertheless, there is hope that the panel may eventually evolve into a formal Shariah Court if it is properly managed and strategically developed. The paper advocates for the establishment of similar Shariah Panels in other South Western Nigerian states that currently lack such institutions and recommends training initiatives for panel members to further enhance their knowledge, skills, and adjudicative capabilities.